(untitled) (Research, Society and Development, 2022)
The aim of the study was to investigate the effects of auriculotherapy and cupping therapy on the improvement of pain in employees of a higher education institution. It is an experimental, descriptive field research with a quantitative approach. Held at a reference University Center in Teresina - PI, from February to June 2022, the sample consisted of 8 employees of the aforementioned Institution. For data collection, we used our own questionnaire, the visual analogue pain scale (VAS) and a validated questionnaire, called Brief Pain Inventory, before and after treatment. The study data were compiled and statistically analyzed using SPSS 22.0 software for Windows and Excel 2022. The study was predominantly male, 75% (n=6), with a mean age of 29 years, and most employees 50% perform the role of faculty at the institution (n=4). After treatment, there was a decrease in pain and pain intensity, in addition to an improvement in mood, sleep and work performance.